On So-Called Novel and Regular Metonymies. (17th January 2020) - Brdar, Mario
Abstract: Two issues pertaining to the use of metonymy that plays a central role in Slabakova et al. (2016) are mentioned in the very title of their study—novel metonymy and regular metonymy. In this article I draw attention to some problems with the identification of these as well as with the assumption that these are opposites of each other.